2016
DOI: 10.1111/jnc.13756
|View full text |Cite
|
Sign up to set email alerts
|

Activation of σ1 and σ2 receptors by afobazole increases glial cell survival and prevents glial cell activation and nitrosative stress after ischemic stroke

Abstract: Activation of sigma receptors at delayed time points has been shown to decrease injury following ischemic stroke. The mixed σ1/σ2 receptor agonist, 5-ethoxy-2-[2-(morpholino)-ethylthio]benzimidazole (afobazole), provides superior long-term outcomes compared to other σ ligands in the rat middle cerebral artery occlusion (MCAO) stroke model. Experiments using the MCAO model were carried out to determine the molecular mechanism involved in the beneficial effects of afobazole. Administration of afobazole (3 mg/kg)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 42 publications
1
14
0
Order By: Relevance
“…Experiments in our laboratory have shown that σ receptor activation with afobazole can reduce activation of microglia and lessen microglial cell death in vitro and in vivo (Cuevas et al, 2011b; Katnik et al, 2016). Previous studies have shown that following an ischemic stroke there is an increase in ATP release, which leads to activation and migration of microglial cells (Davalos et al, 2005).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Experiments in our laboratory have shown that σ receptor activation with afobazole can reduce activation of microglia and lessen microglial cell death in vitro and in vivo (Cuevas et al, 2011b; Katnik et al, 2016). Previous studies have shown that following an ischemic stroke there is an increase in ATP release, which leads to activation and migration of microglial cells (Davalos et al, 2005).…”
Section: Resultsmentioning
confidence: 99%
“…Ischemic stroke has been shown to be a multicellular disease, and any attempts to treat this disease must target several cell types (Hall et al, 2009b; Leonardo et al, 2010; Cuevas et al, 2011a,b). Neurons have previously been the primary target in the treatment of stroke, but microglia and astrocytes play a dynamic role in the pathophysiology of stroke (Hu et al, 2012; Katnik et al, 2016; Xu et al, 2017). In response to stroke or other types of CNS injury, microglia become activated and migrate to the site of injury (Kierdorf and Prinz, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Afobazole decreased the microglial cells migration induced by nucleoside triphosphates and amyloid Aβ 25–35 in vitro [ 80 , 81 ]. In an in vivo model of ischemic stroke, afobazole prevents glial activation and death, while selective Sigma1R antagonists blocked the effect of the drug [ 77 ]. These stimuli of afobazole correspond to Sigma1R activation [ 58 ] and the neuroprotective effect of PRE-084 in the model of 6-OHDA-induced PD accompanied by the inhibition of microglia migration in SNc [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Afobazole has an affinity to chaperone Sigma1R (Ki = 5.9 µM) and regulatory sites of ribosyldihydronicotinamide dehydrogenase [quinone] (NQO2, Ki = 0.97 µM) and monoamine oxidase A (MAO-A, Ki = 3.6 µM) [ 74 , 75 ]. In vitro and in vivo experiments suggest a role of Sigma1R in the mechanisms of previously described cytoprotective [ 76 ] and neuroprotective [ 77 , 78 , 79 , 80 , 81 , 82 ] properties of afobazole. Afobazole restored DA content in the striatum of mice with unilateral intrastriatal 6-OHDA lesions [ 83 ].…”
Section: Introductionmentioning
confidence: 93%